2013
DOI: 10.1021/jz401310j
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Adsorption of Nitric Acid at the Surface of Amorphous Solid Water Revealed by X-ray Absorption Spectroscopy

Abstract: A spectral feature unique to the molecularly adsorbed state of HNO 3 is found in X-ray absorption spectroscopy. This distinctive signature reveals the extent to which nitric acid is ionically dissociated upon its adsorption on amorphous solid water (ASW) at low coverage and low temperature. Thermal annealing induces irreversible proton transfer from HNO 3(ads) , demonstrating that it is metastable with respect to ionic dissociation below 100 K at the surface of ASW. The slight decrease in ionic dissociation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Indeed, previous X-ray absorption 52 and infrared spectroscopic 55 studies have reported that NO3 -anions (arising from ionic dissociation of HNO3 adsorbed onto ASW) diffuse within the underlying substrate on an experimentally observable time scale at or near this temperature (i.e., albeit to a depth of <50 Å according to Marcotte et al). 52 Therefore, as nitrate anions cannot be kinetically trapped at the surface of ASW at 120 K, and because they have diffused within the ASW substrate, the behavior (i.e., photolysis rate, asym-NOstr splitting) of surface nitrates samples (Figure 2A, open blue triangles) is more akin to that of bulk nitrates samples (Figure 2A, filled blue triangles). Accordingly, the photo-destruction rates of NO3 -anions in surface nitrates samples only displays a significant enhancement over those of bulk nitrates samples at 70 K and 100 K (Figure 2A and 2B).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, previous X-ray absorption 52 and infrared spectroscopic 55 studies have reported that NO3 -anions (arising from ionic dissociation of HNO3 adsorbed onto ASW) diffuse within the underlying substrate on an experimentally observable time scale at or near this temperature (i.e., albeit to a depth of <50 Å according to Marcotte et al). 52 Therefore, as nitrate anions cannot be kinetically trapped at the surface of ASW at 120 K, and because they have diffused within the ASW substrate, the behavior (i.e., photolysis rate, asym-NOstr splitting) of surface nitrates samples (Figure 2A, open blue triangles) is more akin to that of bulk nitrates samples (Figure 2A, filled blue triangles). Accordingly, the photo-destruction rates of NO3 -anions in surface nitrates samples only displays a significant enhancement over those of bulk nitrates samples at 70 K and 100 K (Figure 2A and 2B).…”
Section: Resultsmentioning
confidence: 97%
“…This is best illustrated by the arrows in Figure 1 that display the evolution in the bands' barycenter as a function of irradiation time. Unfortunately, attempts to identify the spectral signatures of the possible/expected nitrates photolysis reaction products with RAIRS 55 and NEXAFS 52 remain unsuccessful. Surface nitrates samples were created by adsorbing 0,4 L HNO3 onto a 10 L dense ASW film while bulk nitrates samples (~5% mole fraction) were prepared by simultaneous condensation of HNO3 and H2O vapours on a gold substrate under conditions known to yield extensive ionic dissociation of HNO3.…”
Section: Resultsmentioning
confidence: 99%
“…Another pioneering application of NAPP was the confirmation of the uptake of trace gases to ice, namely acetone [61] and acetic acid [32], which is a relevant process for environmental science, but directly linked also to catalytic research. Core level spectroscopy has successfully shown that strong acids are predominately ionized on amorphous solid water at 90 K leading to the suggestion of primal dissociation on ice at temperatures relevant to the Earth's environment [62,63]. The only study that directly observed the degree of protonation and the structure of the hydrogenbonding network at low dosage at the ice surface at temperatures of 240 K was recently published by our group [51].…”
Section: Uptake Of Trace Gases To Icementioning
confidence: 99%
“…(22) Features e and f at LT are distinctive, and they match similarly sharp features seen in the O 1s XANES spectra of amorphous solid water. (23,24) Theoretical simulations of water also show strong features at the appropriate energies, but only when broken hydrogen bonds (specifically with dangling hydrogens) are present. (25) Thus, previous work on amorphous solid water shows many spectroscopic similarities to the O 1s data in Figure 1.…”
Section: Samplementioning
confidence: 99%